Optimization model to minimize feed costs portions standing (lifting, fattening and finishing) - Ojeda Enríquez, Miguel; Quevedo Buitrago, Jorge; Gámez Manchola, Natalia (Scientia et Technica, 2018)
The efficient feeding of growing pigs is one of the most important practices of a pig farm, because both the production yield and the profitability of the farm depend on it. Feeding accounts for 80 to 85% of total production costs. For this reason, a linear optimization model was formulated and designed at minimum cost for the management of information of pig production on its feet (lifting, fattening and finishing) for the farm "La Esperanza" in Tierra Negra Fusagasugá (Cundinamarca). The percentages of the practical and maximum levels of inclusion of food in pork rations in growth given by the Spanish Foundation for the development of animal nutrition FEDNA in 2016 were managed to reach the restrictions of feeding and costs per kilogram in each stage. These data were used for the mathematical model in which it was adjusted to the two-phase Simplex Method. For which a prototype of web-oriented software was developed with a simple, simple and friendly design, applying good practices to solve it. For the development of this project, programming languages such as PHP with the Object oriented Programming paradigm, MySQL database and technologies such as HTML5, CSS and JavaScript were used. They helped to guarantee the security and integrity of the data, allowing us to build a quality code, safe and easy to maintain. It was determined that the application easily enters decision variables, the objective function and constraints of each linear optimization model, giving a final report of the results obtained. The mathematical model allowed to give a new feeding formula according to the percentage applied to the bulk of each raw material in the ton, allowing a significant reduction in feed costs in pigs per ton produced.